“Fiat Lux.” Navigating chaos through Sensing Leadership - van der Merwe, Johan (Stellenbosch Theological Journal, 2018)
This article provides an overview of change management strategies described in business science. From the distinctions made, it becomes clear that change is all-pervasive and the result of complex interactions within and between the internal and external environments of organizations and communities. Complexity theory is subsequently considered as a better vantage point from where a response to change may be informed. The leadership style to correspond to this new reading of change needs to be that of “transcending leadership” where sensing and sense-making skills are honed to sense emerging meaning in organizations, in interpersonal relationships and through intrapersonal reflection. Instead of “making” change happen, the new leadership “lets” things happen, sensing the connections between emerging events in the context and creating a level of readiness to find the potential meaning in what may usually have been perceived as mere chaos. The creation narrative and a new reading of chaos as possibility provide Judeo-Christian sources of spirituality in this regard. Other Biblical narratives are cited to show in which way different change management frameworks can be applied to the respective narratives, but also how sensing and sense-making remain the common leadership attributes in successfully navigated change.